Comparison of Clinical Efficacy and Safety of Metformin Sustained-Release Tablet (II) (Dulening) and Metformin Tablet (Glucophage) in Treatment of Type 2 Diabetes Mellitus - Guo, Li-xin; Liu, Guo-en; Chen, Li; Wang, Hai-fang; Guo, Jian; Zheng, Xian-ling; Duan, Bin-hong; Wang, De-zhong; Zhu, Wei; Wang, Kun; Tan, Wan-shou; Chen, Qiu; et al. (Frontiers in Endocrinology, 2021)
Objectives This study investigated the clinical efficacy and safety of metformin hydrochloride sustained-release (SR) tablet (II) produced by Dulening and the original metformin hydrochloride tablet produced by Glucophage in the treatment of type 2 diabetes mellitus (T2DM). Methods This randomized, open and parallel controlled clinical trial consecutively recruited a total of 886 patients with T2DM in 40 clinical centers between May 2016 and December 2018. These patients were randomly assigned to the Dulening group (n=446), in which patients were treated with Dulening metformin SR tablets, and the Glucophage group (n=440), in which patients were treated with Glucophage metformin tablets, for 16 weeks. The changes in the levels of glycated hemoglobin (HbAc1) and fasting blood glucose (FBG) as well as weight loss were compared between these two groups. Also, the overall incidence of adverse drug reactions (ADRs) and the incidence of ADR of the gastrointestinal system observed in patients of these two groups were also compared. Results There were no significant differences in demographic and basal clinical characteristics between these two groups. The Dulening and Glucophage groups showed comparable levels of decrease in HbA1c levels, FBG and weight loss after 12-week treatment (all p>0.05). The Dulening group had a significantly lower overall incidence of ADRs as well as gastrointestinal ADR than the Glucophage group. Conclusions Metformin SR tablets (II) and the original metformin tablets exhibit similar therapeutic efficacy in the treatment of T2DM, but metformin SR tablets (II) has the significantly lower incidence of ADRs than the original metformin tablets.